Correlation between teacher personality and professional development literacy of teachers at SMK YAPPA Depok - Solihatun Solihatun; Yulian Dinihari; Gilang Rizkia Aditia; Dieta Putri Rachmat; Sulis Setioharti Handayani; Burju Ruth; Ajeng Radyati (Institute of Computer Science (IOCS), 2026)
In the Merdeka Curriculum framework, teachers serve as agents in implementing adaptive, learner-centered instruction. Accordingly, teacher development extends beyond pedagogical and professional competencies and is connected to personality competence as an internal foundation of professional practice. Teacher personality is assumed to influence professional development literacy, defined as teachers’ capacity to understand, plan, implement, and reflect on continuous professional growth. However, empirical evidence examining this relationship remains limited, particularly in vocational education contexts. This study aims to analyze the relationship between teacher personality and professional development literacy among teachers at SMK YAPPA Depok. The null hypothesis states that no relationship exists between the variables, whereas the alternative hypothesis assumes a significant relationship. A quantitative descriptive-correlational design was employed, involving all fifteen teachers through a saturated sampling technique. Data were analyzed using descriptive statistics and Spearman’s Rho correlation due to non-normal data distribution and ordinal measurement scales. The results indicate that teacher personality and professional development literacy are generally at moderate to high levels, with variation among respondents. Furthermore, correlation analysis reveals a significant relationship between teacher personality and professional development literacy, leading to rejection of the null hypothesis. These findings highlight the role of teacher personality in strengthening professional development literacy.